Continuing to look in the mirror: A review of neuroscientific evidence for the broken mirror hypothesis, EP-M model and STORM model of autism spectrum conditions. (November 2020) - Yates, Luke; Hobson, Hannah
The mirror neuron system has been argued to be a key brain system responsible for action understanding and imitation. Subsequently, mirror neuron system dysfunction has therefore been proposed to explain the social deficits manifested within autism spectrum condition, an approach referred to as the broken mirror hypothesis. Despite excitement surrounding this hypothesis, extensive research has produced insufficient evidence to support the broken mirror hypothesis in its pure form, and instead two alternative models have been formulated: EP-M model and the social top-down response modulation (STORM) model. All models suggest some dysfunction regarding the mirror neuron system in autism spectrum condition, be that within the mirror neuron system itself or systems that regulate the mirror neuron system. This literature review compares these three models in regard to recent neuroscientific investigations. This review concludes that there is insufficient support for the broken mirror hypothesis, but converging evidence supports an integrated EP-M and STORM model. Lay abstract: The mirror neuron system has been argued to be a key brain system responsible for understanding the actions of others and for imitation. It has therefore been proposed that problems within this system could explain the social difficulties experienced by people with autism spectrum condition. This idea is referred to as the broken mirror hypothesis. However, research has produced insufficient evidence to support the broken mirror hypothesis in its original form. Therefore, two other models have been suggested: EP-M model and the social top-down response modulation (STORM) model. All models suggest something is different regarding the mirror neuron system in autism spectrum condition: either within the mirror neuron system itself or within the systems that control the activity of the mirror neuron system. This literature review compares these three models in regard to recent neuroscientific investigations. This review concludes that there is insufficient support for both the broken mirror hypothesis, but converging evidence supports an integrated EP-M and STORM model.